2013
DOI: 10.1111/jmwh.12022
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacology of Prostaglandins for Induction of Labor

Susan M. Yount,
Nicole Lassiter

Abstract: Prostaglandin medications are frequently used in the process of induction of labor. Understanding the history and research that supports prostaglandin use for induction of labor is crucial for safe practice. Dinoprostone has been the standard of care for cervical ripening in term pregnancies. Misoprostol administration via various routes has been shown to be efficacious. Oral misoprostol in particular is effective and associated with reassuring maternal and fetal outcomes. In addition, cost has become a variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
(354 reference statements)
1
26
0
1
Order By: Relevance
“…Prostaglandins function to promote cervical ripening and increase myometrial contractility, whereas oxytocin stimulates uterine contractions, primarily by increasing intracellular calcium. 25,26 In patients with intact membranes undergoing cervical ripening and induction of labor, oxytocin is not as effective as prostaglandin American Journal of Perinatology methods. 27 However, other studies have shown that induction of labor with oxytocin and amniotomy is one of the most effective methods at achieving vaginal delivery within 24 hours, and that early amniotomy in nulliparous patients undergoing induction of labor shortens the time to delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Prostaglandins function to promote cervical ripening and increase myometrial contractility, whereas oxytocin stimulates uterine contractions, primarily by increasing intracellular calcium. 25,26 In patients with intact membranes undergoing cervical ripening and induction of labor, oxytocin is not as effective as prostaglandin American Journal of Perinatology methods. 27 However, other studies have shown that induction of labor with oxytocin and amniotomy is one of the most effective methods at achieving vaginal delivery within 24 hours, and that early amniotomy in nulliparous patients undergoing induction of labor shortens the time to delivery.…”
Section: Resultsmentioning
confidence: 99%
“…In most countries, doctors are prone to use dinoprostone in the form of a vaginal insert for unprepared cervix. However, both vaginal insert and gel are recognized to be equally effective in overall time to mode of birth and neonatal outcome . Misoprostol has been used for induction of labor since the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is an increased risk of excessive contractile function (hyperstimulation) associated with this method. Currently, the most commonly used drug to pre-induct the labor is dinoprostone, which is a PGE2 analog and misoprostol, aPGE1 analog [6].…”
Section: Introductionmentioning
confidence: 99%